2010
DOI: 10.1101/gad.604610
|View full text |Cite
|
Sign up to set email alerts
|

SMG6 interacts with the exon junction complex via two conserved EJC-binding motifs (EBMs) required for nonsense-mediated mRNA decay

Abstract: Nonsense-mediated mRNA decay (NMD) is a quality control mechanism that detects and degrades mRNAs containing premature stop codons (PTCs). In vertebrates, PTCs trigger efficient NMD when located upstream of an exon junction complex (EJC). Degradation of PTC-containing mRNAs requires the endonucleolytic activity of SMG6, a conserved NMD factor; nevertheless, the precise role for the EJC in NMD and how the SMG6 endonuclease is recruited to NMD targets have been unclear. Here we show that SMG6 interacts directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
71
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 38 publications
(79 reference statements)
7
71
0
Order By: Relevance
“…Consistent with a dependence of NMD on translation termination, Upf1 interacts with the release factors eRF1 and eRF3 in humans and yeast, possibly to function in termination events using its helicase and RNA binding activities (Czaplinski et al 1998;Wang et al 2001;Ghosh et al 2010). In vertebrates, Upf1 and its regulator Smg-1 interact with the release factors forming the SURF (Smg-1-Upf1-Release factors) complex, and this SURF-associated Upf1 appears to be able to interact with Upf2-Upf3 bound to the exon junction complex (Yamashita et al 2009;Kashima et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a dependence of NMD on translation termination, Upf1 interacts with the release factors eRF1 and eRF3 in humans and yeast, possibly to function in termination events using its helicase and RNA binding activities (Czaplinski et al 1998;Wang et al 2001;Ghosh et al 2010). In vertebrates, Upf1 and its regulator Smg-1 interact with the release factors forming the SURF (Smg-1-Upf1-Release factors) complex, and this SURF-associated Upf1 appears to be able to interact with Upf2-Upf3 bound to the exon junction complex (Yamashita et al 2009;Kashima et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The EJC is a multimeric protein complex deposited by the splicing machinery 24 nt upstream of the spliced exon-exon boundary in metazoans (Le Hir et al 2000;Sauliere et al 2012;Singh et al 2012). The EJC core consists of the four proteins eIF4AIII, Y14, MAGOH, and MLN51 (also known as Barentz) (Andersen et al 2006;Bono et al 2006), and additional factors associate with the EJC core in a dynamic way, including Pinin, SKAR, SRm160, RNPS1, Acinus, SAP18, UAP56, Aly/REF, and the two NMD factors UPF3b and SMG6 (Le Hir et al 2000Kashima et al 2010;Bono and Gehring 2011;Murachelli et al 2012). UPF3b binds the EJC core via its C-terminal low-complexity region (Gehring et al 2003;Buchwald et al 2010), and two conserved EJC-binding motifs (EBMs) were identified in the N-terminal part of SMG6 that interact with essentially the same surface on the EJC core as UPF3b (Kashima et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The EJC core consists of the four proteins eIF4AIII, Y14, MAGOH, and MLN51 (also known as Barentz) (Andersen et al 2006;Bono et al 2006), and additional factors associate with the EJC core in a dynamic way, including Pinin, SKAR, SRm160, RNPS1, Acinus, SAP18, UAP56, Aly/REF, and the two NMD factors UPF3b and SMG6 (Le Hir et al 2000Kashima et al 2010;Bono and Gehring 2011;Murachelli et al 2012). UPF3b binds the EJC core via its C-terminal low-complexity region (Gehring et al 2003;Buchwald et al 2010), and two conserved EJC-binding motifs (EBMs) were identified in the N-terminal part of SMG6 that interact with essentially the same surface on the EJC core as UPF3b (Kashima et al 2010). EJCs located in the 5 ′ UTR and coding sequence of an mRNA are disassembled by the elongating ribosome by a process that involves the ribosome-bound protein PYM (Gehring et al 2009b;Bono and Gehring 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Smg6 is thought to be recruited to target mRNAs by virtue of its 14-3-3-like domain, which can bind phosphorylated Upf1 (Fukuhara et al 2005). In mammalian cells, Smg6 is also recruited to target mRNAs through direct recruitment to the EJC (Kashima et al 2010). Smg6 function has primarily been analyzed in cell culture, and while some genetic analysis has been performed in C. elegans (Hodgkin et al 1989;Page et al 1999), a role for SMG-6 endonuclease function has not yet been analyzed in this organism.…”
Section: Introductionmentioning
confidence: 99%